2018
DOI: 10.3390/f9010025
|View full text |Cite
|
Sign up to set email alerts
|

Ash Dieback on Sample Points of the National Forest Inventory in South-Western Germany

Abstract: Abstract:The alien invasive pathogen Hymenoscyphus fraxineus causes large-scale decline of European ash (Fraxinus excelsior). We assessed ash dieback in Germany and identified factors that were associated with this disease. Our assessment was based on a 2015 sampling of national forest inventory plots that represent a supra-regional area. In the time from 2012 to 2015, the number of regrown ash trees corresponded to only 42% of the number of trees that had been harvested or died. Severe defoliation was recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 26 publications
2
33
0
3
Order By: Relevance
“…Stronger plants had an improved chance of surviving either an H. fraxineus or Phytophthora attack (Table 3), which correlates with studies showing that damage to developed trees is less frequent [16,18]. A positive correlation was observed between the height and diameter of seedlings and their survival, and also the height/diameter interaction was strong and significant.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Stronger plants had an improved chance of surviving either an H. fraxineus or Phytophthora attack (Table 3), which correlates with studies showing that damage to developed trees is less frequent [16,18]. A positive correlation was observed between the height and diameter of seedlings and their survival, and also the height/diameter interaction was strong and significant.…”
Section: Discussionsupporting
confidence: 80%
“…The mortality of seedlings in ash stands infected with H. fraxineus constitutes major damage and a threat to the existence of the species on the sites [16,52]. The regeneration of ash on heavily infested sites is endangered both by infestation and a lower production of seed [53], and by a high infection rate of seedlings [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It started in north-eastern Poland and during the next years expanded to neighboring countries (Przybył 2002;Bakys et al 2009a;Pautasso et al 2013;Gross et al 2014a). Recently, a severe dieback of ash, which includes trees in all age stages (Gross et al 2014a;Needham et al 2016;Enderle et al 2018), can be observed in most European countries (Bakys et al 2009a, b;Kowalski and Holdenrieder 2009a, b;Allen et al 2010;Beck et al 2016;Coker et al 2019). It is caused mainly by the fungus Hymenoscyphus fraxineus, which induces wilting and loss of leaves, thinning of crowns, darkening of wood, necrosis and neoplastic changes on trunks and branches, and finally leads to the deaths of trees (Baral et al 2014;Gross et al 2014b), but other pathogens that weaken this tree are also reported, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Global warming and globalization put pressure on forests ecosystems and threaten their capacity to deliver goods and services to society 1,2 . In the last centuries, an increasing number of invasive pathogens have been introduced into forests 3 mainly by trade of living plants, which has created an unprecedented movement of species across continents [4][5][6] .…”
mentioning
confidence: 99%